Peran E Business dalam Pengembangan UMKM dengan Memanfaatkan Digital Marketing - Ade Kurnia Sari; Kharisma Syahputri; Nurbaiti Nurbaiti (Trending: Jurnal Manajemen dan Ekonomi, 2024)
In the post-COVID-19 pandemic era, Micro, Small and Medium Enterprises (MSMEs) are experiencing radical changes in their operational landscape due to advances in information technology, especially through E-business and digital marketing. The impact of the pandemic has caused a significant decline in sales, distribution and access to finance for MSMEs. As a result, MSMEs are now focusing more on digital business models compared to conventional offline strategies, by utilizing social media and online markets as broad marketing channels. This research highlights how digital marketing and E-business are revolutionizing the way MSMEs interact with the market. By implementing digital marketing strategies, MSMEs can expand their global market reach, increase visibility through SEO techniques, personalize interactions with customers, and speed up customer service and inventory management. Changes in consumer behavior, such as reduced brand loyalty, the importance of product reviews, and decreased consumer tolerance, must be addressed. To remain competitive in this increasingly digital business environment, MSMEs must adapt to these changing trends, make optimal use of digital resources, and build strong customer relationships.